1986
DOI: 10.1210/endo-118-1-393
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Noncoordinate Regulation ofα-Lactalbumin and 25 Kβ-Casein by Corticosterone, Prolactin, and Insulin in Long Term Cultures of Normal Rat Mammary Cells*

Abstract: The concentrations of PRL, corticosterone, and insulin required by long term cultures of normal rat mammary cells to produce alpha-lactalbumin (alpha LA) and the 25,000 mol wt beta-casein were evaluated with a variety of hormone ratios and concentrations. For these studies a double antibody RIA for beta-casein capable of measuring 0.5 ng beta-casein/100 microliter growth media was developed and used along with our previously reported RIA for alpha LA. PRL was active at physiological levels (0.05-0.15 microgram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In fact, a degree of hormonally controlled gland development and secretion may have predated substantial glandular hypertrophy, particularly if mammary glands are more closely related to sebaceous glands than to sweat glands. Prolactin is known to affect the growth and activity of sebaceous glands and mammary glands (Ebling, 1967;Nicoll & Bern, 1972), as well as a-lactalbumin and casein synthesis (Rosen, 1981;Ray et al, 1986). An investigation of the effects of prolactin on lysozyme synthesis may prove enlightening in this regard.…”
Section: Following Divergence Ofmentioning
confidence: 99%
“…In fact, a degree of hormonally controlled gland development and secretion may have predated substantial glandular hypertrophy, particularly if mammary glands are more closely related to sebaceous glands than to sweat glands. Prolactin is known to affect the growth and activity of sebaceous glands and mammary glands (Ebling, 1967;Nicoll & Bern, 1972), as well as a-lactalbumin and casein synthesis (Rosen, 1981;Ray et al, 1986). An investigation of the effects of prolactin on lysozyme synthesis may prove enlightening in this regard.…”
Section: Following Divergence Ofmentioning
confidence: 99%
“…RIAs of HMFG2 (Burchell et al, 1984), DF3 antigen (Hayes et al, 1985) and MAM6 antigen (Hilkens et al, 1984) have also shown high levels of the respective antigens in ovarian carcinoma. It may be that gynaecological tumours to produce and secrete milk proteins (Ray et al, 1986). However, the distinction between breast and gynaecological cancers is not a diagnostic problem.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids have been shown to regulate various aspects of MEC branching morphogenesis and when provided in combination with insulin andlor prolactin induce the cytological and functional differentiation of MEC (Ray et al, 1986;Rosen et al, 1986;Hurley et al, 1989;Doppler et al, 1990;Puissant and Houdebine, 1991;Zettl et al, 1992). The specific role that steroids, polypeptides, ECM components, and mammary gland parenchymal as well as mesenchymal cells play in modulating the type, magnitude, andlor persistance of the epithelial cell-specific effects induced by glucocorticoids has not been clearly established.…”
Section: Epithelial Cell-specific Effects Of Hydrocortisonementioning
confidence: 99%
“…Our findings indicate the hydrocortisone was required for the induction and maintenance of multilobular alveolar morphogenesis as well as the production and accumulation of casein and lipid. Additional studies will be required to determine whether the mechanism responsible for the reduction in the levels of accumulated casein involves the participation of MEC-derived proteins with caseinolytic activity or the downregulation of casein transcription and/or synthesis (Ray et al, 1986;Rosen et al, 1986;Dopper et al, 1990). Taken together, the morphological and biochemical changes suggest that a reversion in the functional capacity of the MEC does not have to involve the induction of apoptosis.…”
Section: Reversibility Of the Hydrocortisone-mediated Effectsmentioning
confidence: 99%